Sovereign risk contagion in the Eurozone: A time-varying coefficient approach - Alexander Ludwig (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2013)
This paper analyzes sovereign risk contagion in the Eurozone using an extension to the canonical model for contagion proposed by Pesaran and Pick (2007) and Metiu (2012) to allow for time-varying coefficients. This becomes necessary due to changes in the risk pricing of sovereign bonds since the onset of the recent crisis period and due to the presence of contagion in typically bounded time intervals. Controlling for changes in the risk pricing by investors, we detect several channels of pure contagion between 2008 and 2012. Further, we find that the bailout-programs for Greece, Ireland and Portugal led to a disruption in contagion of sovereign risk from these countries to Spain, Italy, France and Belgium as was desired by policymakers. For all countries considered, we observe an increase in the relevance of general risk aversion towards sovereign debt since May 2010. This development partially replaced the significance of country-specific credit risk factors in explaining bond yield spreads. Our model extension yields a device that is suitable to determine whether policy interventions are required and to judge their success ex-post.
Keywords: C32; E44; G01; G15; 330; contagion; credit events; Eurozone; financial crisis; sovereign risk; time-varying approach